Protective effects of mitochondrial fission inhibition on ox-LDL induced VSMC foaming via metabolic reprogramming - Fang, Yijin; Zhu, Yu; Wu, Yue; Liu, Liangming; Wang, Huadong (Frontiers in Pharmacology, 2022)
Atherosclerosis (AS) is one of the most common diseases in middle-age and elderly population. Lipid metabolism disorder induced foaming of vascular smooth muscle cell (VSMC) is an important pathological process of AS. Mitochondria plays an important role in lipids metabolism. While it is not known whether regulating mitochondrial function can protect ox-LDL induced VSMC foaming via metabolic reprogramming. With ox-LDL induced mouse model of VSMC injury, the injury effect of ox-LDL and the protective effect of mdivi-1, the mitochondrial fission inhibitor on mitochondrial morphology and function of VSMC, and the formation of lipid droplet were observed. With metabonomics and proteomics techniques, the main lipid metabolites and regulation proteins were identified. The results showed that Ox-LDL induced a significant mitochondrial fission and fragmentation of VSMC, and mitochondrial function disorder along with lipid deposition and foaming. Mdivi-1 significantly antagonized the damage effect of ox-LDL on mitochondrial morphology and function of VSMC, and blocked the lipid deposition. Metabonomics analysis found 848 different metabolites between ox-LDL and mdivi-1 treatment group, in which the lipid metabolites were the main, and heptadecanoic acid, palmitoleic acid and myristic acid were the critical metabolites changed most. Proteomics results showed that there were 125 differential expressed proteins between ox-LDL and mdivi-1 treatment, acetyl -CoA carboxylase1 and fatty acid synthase were the main differential expressed proteins. This study suggest that Mitochondrial fission plays an important role in VSMC lipid deposition and foaming. Inhibition of mitochondrial fission may effectively fight against ox-LDL induced lipid deposition and foaming of VSMC via improving mitochondrial function and metabolic reprogramming. This finding provides a new insight for prevention and treatment of AS.